2015
DOI: 10.1007/s00396-015-3731-4
|View full text |Cite
|
Sign up to set email alerts
|

Halloysite nanotubes as a stabilizer: fabrication of thermally expandable microcapsules via Pickering suspension polymerization

Abstract: Core-shell thermally expandable microcapsules were prepared via Pickering suspension polymerization. Acrylonitrile (AN) and methyl methacrylate (MMA) were used as the comonomers and the halloysite nanotubes (HNTs) were used as the Pickering emulsifier. The influence of the HNT concentration, AN/MMA ratio, and types of hydrocarbon was investigated. When the HNT concentration was 0.6 wt%, the microcapsules exhibited a core-shell morphology that contained approximately 35 wt% of the blowing agents with an average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Kim et al . reported that adding a small amount of hydroquinone would minimize this effect . It can be seen from the SEM images that the TEMs were not spherical in shape, probably due to the liquid hydrocarbon in the core.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al . reported that adding a small amount of hydroquinone would minimize this effect . It can be seen from the SEM images that the TEMs were not spherical in shape, probably due to the liquid hydrocarbon in the core.…”
Section: Resultsmentioning
confidence: 99%
“…The prepared TEMs with two different type of stabilizer were tested for use as blowing agents during injection molding, in order to determine the difference between the final products. It is noted that halloysite nanotubes have not been used as steric stabilizers for TEMs …”
Section: Introductionmentioning
confidence: 94%
“…also prepared relatively uniform particle sizes consisting of a n ‐octane/poly(acrylonitrile‐ co ‐methyl methacrylate) core–shell structure using low‐temperature initiators by suspension polymerization. Kim et al . used halloysite nanotubes as a stabilizer to fabricate thermally expandable microcapsules via suspension polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…These thermally expandable capsules were expanded by the evaporation of blowing materials in the core through thermal treatment at temperatures above the glass transition temperature ( T g ) . The capsules were mainly synthesized using suspension polymerization to make use of polymer barrier properties for effective expansion . The physical properties of the aforementioned capsules depend on the constituent polymer; for example, polyacrylonitrile and poly(methacrylonitrile) can effectively prevent gas release and are frequently used as capsule shell components .…”
Section: Introductionmentioning
confidence: 99%